Antigenic Variation of Avian Influenza A(H5N6) Viruses, Guangdong Province, China, 2014-2018 - Bai, Ru; Sikkema, Reina S; Li, Cong Rong; Munnink, Bas B Oude; Wu, Jie; Zou, Lirong; Jing, Yi; Lu, Jing; Yuan, Runyu; Liao, Ming; Koopmans, Marion P G; Ke, Chang-Wen (Emerging infectious diseases, 2019)
Market surveillance showed continuing circulation of avian influenza A(H5N6) virus in live poultry markets in Guangdong Province in 2017, despite compulsory vaccination for avian influenza A(H5Nx) and A(H7N9). We analyzed H5N6 viruses from 2014-2018 from Guangdong Province, revealing antigenic drift and decreased antibody response against the vaccine strain in vaccinated chickens.